2009
DOI: 10.1007/s00253-009-1925-8
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of model phenolic compounds in lignocellulosic hydrolysates with peroxidase for butanol production from Clostridium beijerinckii

Abstract: In the present study, we investigated the peroxidase-catalyzed detoxification of model phenolic compounds and evaluated the inhibitory effects of the detoxified solution on butanol production by Clostridium beijerinckii National Collection of Industrial and Marine Bacteria Ltd. 8052. The six phenolic compounds, p-coumaric acid, ferulic acid, 4-hydroxybenzoic acid, vanillic acid, syringaldehyde, and vanillin, were selected as model fermentation inhibitors generated during pretreatment and hydrolysis of lignocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(75 citation statements)
references
References 31 publications
1
72
0
2
Order By: Relevance
“…It was reported that, during the initial growth phase of cells, other by-products were also produced such as acetic acid and butyric acid, which inhibited the butanol production [84]. In one study, the presence of 1 g/l ferulic acid and vanillin acid reduced the cell growth by 70% and 56%, respectively [84]. The choice of detoxification method would depend on the compositions of hydrolysates and the species of fermenting microorganism [84].…”
Section: Eliminating Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that, during the initial growth phase of cells, other by-products were also produced such as acetic acid and butyric acid, which inhibited the butanol production [84]. In one study, the presence of 1 g/l ferulic acid and vanillin acid reduced the cell growth by 70% and 56%, respectively [84]. The choice of detoxification method would depend on the compositions of hydrolysates and the species of fermenting microorganism [84].…”
Section: Eliminating Inhibitorsmentioning
confidence: 99%
“…In one study, the majority of inhibitory compounds were phenolic compounds, while furfural and hydroxymethyl furfural (HMF) did not affect the cell growth and ABE fermentation [84]. It was reported that, during the initial growth phase of cells, other by-products were also produced such as acetic acid and butyric acid, which inhibited the butanol production [84]. In one study, the presence of 1 g/l ferulic acid and vanillin acid reduced the cell growth by 70% and 56%, respectively [84].…”
Section: Eliminating Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physicochemical detoxification methods are carried out by lime treatment (Njoku et al, 2013;Martínez et al, 2000), activated charcoal Berson et al, 2005), evaporation (Palmqvist, & Hahn-Hagerdal, 2000), ion exchange resins (Cho et al, 2009) or nano-filtration (Sun, & Liu, 2010). The general disadvantage of known methods of physicochemical detoxification is their high cost and/or the formation of large amounts of waste, which increases the burden on the environment.…”
Section: Introductionmentioning
confidence: 99%